The relevance of wholesale electricity market places: The Nordic case - Petr Spodniak; Kimmo Ollikka; Samuli Honkapuro (The Economic and Social Research Institute (ESRI), 2019)
Electricity wholesale markets are undergoing rapid transformation due to the increasing share of distributed and variable renewable energy sources (vRES) penetrating the market. The increasing shares of stochastic wind generation bring along greater deviations between the real time power generation and the day-ahead forecasts of power supply. It is therefore reasonable to assume that trading activity is shifting more from the traditionally dominant day-ahead market into the intra-day and regulating power markets. This is because predicting vRES power generation closer to the actual delivery is more reliable and because power generators are motivated to avoid high imbalance costs. We study price spreads between day-ahead, intra-day and regulating power markets in three Nordic countries (Denmark, Sweden and Finland) during 2013-2017. We estimate vector autoregressive (VAR) models to study the interrelationships between the price spreads and the effects of wind forecast and demand forecast errors, and other exogenous variables, such as transmission congestions, and hydrological conditions, on price spreads in different Nord Pool bidding areas. We use the variation in the shares of wind power between bidding areas to analyse the impacts of increased shares of wind power on different market places. We find that wind forecast errors do affect price spreads in areas with large shares of wind power generation. Moreover, demand forecast errors have an impact on almost all price spreads, except in areas with relatively low consumption. Our results indicate that increasing shares of wind power are, indeed, changing the relevance of different market places. Markets closer to real time are playing more important role than in the past.
Keywords: 330; electricity market; Nordic; wind forecast; demand forecast